Effects of lighting mode on the growth performance, cortisol level and oxidative stress of juvenile Chinese three-keeled pond turtle (Chinemys reevesii) - Li, Haijun; Guo, Jianlin; Zhao, Jian; Ye, Zhangying; Ji, Mingdong; Zhu, Songming (International Journal of Agricultural and Biological Engineering, 2023)
To improve the light environment and welfare of the turtle cultured indoors, the effects of lighting mode on growth performance, cortisol level, and oxidative stress of juvenile Chinese three-keeled pond turtle, Chinemys reevesii, were investigated in this study. The experimental turtles with an initial weight of (5.610.09) g were reared in tanks under four different lighting modes: three groups with light (lighting the basking area and water area, LBW; lighting the water area only, LW; lighting the basking area only, LB) and control group (no light, NL). The experiment was conducted for more than six months, with each group having three replicates. After 203 d of the experiment, the turtle in the LW group exhibited higher weight gain rate (WGR) and a specific growth rate (SGR, %/d) compared to other treatments. Also, results showed that the final body weight of the turtle exposed to LW was higher than that exposed to other treatments. On the physiological level, serum cortisol level in turtles exposed to LW was significantly lower than that in other treatments. Regarding oxidative stress, the level of catalase (CAT) in turtles exposed to LW and LB was significantly lower than that exposed to LBW and NL. The malonaldehyde (MDA) activity in turtles exposed to LW was significantly lower than other treatments. Based on the growth performance and health status, it is suggested that lighting the water area only is the optimal lighting mode for the juvenile three-keeled pond turtle cultured indoors. Keywords: Chinese three-keeled pond turtle, lighting mode, growth, stress response, oxidative stress DOI: 10.25165/j.ijabe.20231604.7656 Citation: Li H J, Guo J L, Zhao J, Ye Z Y, Ji M D, Zhu S M. Effects of lighting mode on growth performance, cortisol level and oxidative stress of juvenile Chinese three-keeled pond turtle (Chinemys reevesii). Int J Agric & Biol Eng, 2023; 16(4): 58–62.